Verification of window properties after 10 years of exploitation: results of measurements in the pavilion laboratory and the climate chamber - Marek Bartko; Pavol Durica (Acta Polytechnica CTU Proceedings)
The article will deal with the analysis of measured data on a plastic window with thermal insulating triple glazing, which is suitable for low-energy or passive houses. The window was installed in 2011 in the test laboratory of the Department of Building Engineering and Urban planning, Faculty of Civil Engineering, University of Žilina (Slovakia), where it was tested under standard indoor climate conditions and real outdoor climate conditions. Surface temperatures on the frame friezes and glass system and heat flux density were recorded at a five-minute time step. In 2020, the window was removed from the laboratory and subsequently tested in a climate chamber. This paper will present the results of these measurements in terms of heat flow density waveforms, heat transfer coefficient, and total solar transmittance through the glazing. Subsequently, a simulation model of this window will be created in the environment of a computational program and its verification based on the measurements will be carried out. A series of calculations will be performed on the tuned model and analyses of the results and comparisons will be presented under the same climatic conditions as during the real measurements recorded by the meteorological station.